PENERAPAN METODE AUDIO – LINGUAL DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS V SDN 7 SINDUE TOBATA - Roslawa, Roslawa; Tahir, Moh.; Nur, Yunidar (BAHASANTODEA, 2017)
The main problem of this research is 1) whether speaking skill of the Fifth – Graders SDN 7 Sindue Tobata Improved after the aplication of audio – lingual method ? how is the step of the aplication of audio-lingual method in improving speaking skill of the Fifth- Graders SDN 7 Sindue Tobata ? This research intends to 1) improve speaking skill the Fifth- Graders SDN 7 Sindue Tobata, and 2) describe steps in the aplication of audio- lingual method in improving speaking skill of the Fifth-Graders SDN 7 Sindue Tobata. Subject of this clasroom action research was 16 students the Fifth-Graders SDN 7 Sindue Tobata. Data source was teachers and students Research design was conducted in four stages such as: pretreatment, treatment, observation, and reflection. Data were collected trough observation and test and were analyzed trough determining individual achievement criteria and classical also determining the average score of students. The result of this reserch reveals that Cycle I has not achieve KKM Of 75 with score total of 1090 and average 68.2, meanwhile Cycle II shows improvement in achieving KKM 75 with average score of 1430 and average 89.4. The achivement of KKM is 75, then the hypothesis of this research is accepted trough the application of audio-lingual method to improve speaking skill of the Fifth-Graders SDN 7 Sindue Tobata.